Research progress of Traditional Chinese Medicine extended care for patients with sleep disorders after stroke (卒中后睡眠障碍中医延续性护理研究进展) - ZHANG Shuai (张帅); WANG Li (王丽); HUANG Chaoping (黄朝萍); LIANG Hui (梁慧); CHENG Jiangyan (李艳敏); TANG Ling (程江艳); (唐玲) (中西医结合护理)
Sleep disorder is a severe and frequent complication in patients after stroke. It is characterized by the high morbidity, poor prognosis and reduced quality of life. The Traditional Chinese Medicine (TCM )extended care has unique advantages in preventing sleep disorders after stroke. This paper summarized the research status of sleep disorder after stroke in perspectives of TCM theory application, TCM preventive treatment and TCM extended care technology, and put forward some thoughts to provide reference for research and clinical nursing practice in the future. (睡眠障碍是脑卒中常见并发症之一, 发病率较高, 且会加重病情, 影响预后, 降低患者生活质量。中医延续性医疗护理在预防中风后睡眠障碍方面具有独特优势。本文综述了脑卒中后睡眠障碍中医理论应用、中医预防和中医延续性医疗护理技术的研究现状, 并提出一些思考, 以期为后续研究和临床护理工作提供参考。)